Interferon lambda 4 rs368234815 TT>δG variant is associated with liver damage in patients with nonalcoholic fatty liver disease. Issue 6 (6th November 2017) - Petta, Salvatore; Valenti, Luca; Tuttolomondo, Antonino; Dongiovanni, Paola; Pipitone, Rosaria Maria; Cammà, Calogero; Cabibi, Daniela; Di Marco, Vito; Fracanzani, Anna Ludovica; Badiali, Sara; Nobili, Valerio; Fargion, Silvia; et al.
Abstract : The interferon (IFN) lambda 3/4 (IFNL3/4) locus, influencing innate immunity regulation, has been associated with the severity of hepatitis and fibrosis progression during chronic hepatitis C infection, while contrasting results were reported in nonalcoholic fatty liver disease. In this study, we examined whether rs12979860 and the linked causal rs368234815 variant encoding for the alternative IFNL4 protein variant are associated with liver fibrosis and damage in a large multicenter cohort of patients at risk of nonalcoholic steatohepatitis. To clarify the mechanism, we also evaluated the impact on IFN‐stimulated gene hepatic expression in a subset of patients. We considered 946 consecutive Italian individuals at risk of nonalcoholic steatohepatitis with liver histology evaluated according to Kleiner. The rs368234815 TT>δG, rs12979860 C>T, and patatin‐like phospholipase‐3 rs738409 C>G polymorphisms were genotyped; and IFN‐stimulated gene hepatic expression (n = 16) was tested by TaqMan assays. We found that the rs368234815 TT allele was independently associated with severe F3‐F4 fibrosis (odds ratio, 1.53; 95% confidence interval, 1.15‐2.31; P = 0.005) and with severe (grade 2‐3) lobular necroinflammation (odds ratio, 1.47; 95% confidence interval, 1.14‐1.88; P = 0.002). The impact of rs368234815 on liver damage was generally more marked in nonobese individuals, where association with severe fibrosis, necroinflammation, and nonalcoholic steatohepatitis was observed ( P < 0.05). IFN‐stimulated genes were hypo‐expressed in the liver of patients carrying the IFNL4 rs368234815 TT/TT genotype ( P < 0.05). Similar results were observed when considering the rs12979860 polymorphism, which was in high linkage disequilibrium with rs368234815 ( R 2 = 0.87). Conclusion: The IFNL4 genotype is associated with severity of fibrosis in nonalcoholic fatty liver disease patients of European ancestry, likely by modulating the activation of innate immunity and necroinflammation. (Hepatology 2017;66:1885–1893)